Auditors' propensity and accuracy in issuing going‐concern modified audit opinions for charities. (18th July 2021) - Yang, Yitang (Jenny); Simnett, Roger; Carson, Elizabeth
Abstract: This paper identifies factors contributing to the auditor's propensity to issue going‐concern modified audit opinions (hereafter, GCOs) for charities and examines their association with subsequent revocation of their charitable status. We find that about 4 percent of charities receive GCOs and these are more likely for those which are smaller, in greater financial distress, received a prior year GCO, and are also affected by dependence on the various types of funding received. After controlling for these factors, Big 4 auditors are less likely to issue GCOs than other audit firms, but there are no differences in their association with subsequent revocation.